A review of domestic hot water consumption profiles for application in systems and buildings energy performance analysis. (January 2018) - Fuentes, E.; Arce, L.; Salom, J.
Abstract: Domestic hot water usage (DHW) accounts for a significant share of energy consumption in different types of buildings. Achieving a detailed characterization of domestic hot water usage profiles is of great relevance, as this information will allow for a more reliable assessment of the energy efficiency of systems and buildings. A deeper knowledge of the features of demand profiles will allow for the design of innovative control strategies based on consumption patterns. In this study, the authors review recent works on hot water consumption profiles in different types of buildings and then synthesize available information for the accurate estimation of the energy consumption resulting from DHW use. Water draw-off consumption patterns specified in national and international technical standards are reviewed and influential parameters on water consumption are identified, including climatic conditions, seasonality, building type and socio-economic factors. State-of-the-art modelling tools for generating DHW usage profiles are summarised and new research lines are then proposed, taking into account the caveats in the current characterization and modelling of DHW consumption in buildings.